Neurotrophins (NTs) and Neurotrophin Receptors (NTRs) as emerging therapeutic paradigm in head and neck tumors - A mini review - Thuckanickenpalayam Ragunathan Yoithapprabhunath; Krubakar RachelSarahVinodhini; Shanmugam Mohanapriya; Joseph Babu Susai Raj; Vasudevan Kalaiselvi; Ramadas Madhavan Nirmal (Wolters Kluwer Medknow Publications, 2020)
Cells of the human biological system emerge from various concerted processes of cell growth, differentiation, repair, and regeneration to a degree. Neurotrophins (NTs) and Neurotrophin Receptors (NTRs) have robust effects on proliferation, differentiation, migration, survival, and synapse formation through physiologic regulatory signals. Dysregulation of such neurotrophic factors not only results in various age-related degenerative conditions but also paves the way to oncogenesis in neuronal and non-neuronal tissues. This review aims to highlight the emerging role of neurotrophins (NTs) and Neurotrophin Receptors (NTRs) in Oral Health and Disease and its molecular signaling pathway in physiologic and pathologic conditions. The electronic databases PubMed, MEDLINE, Scopus, and Google Scholar were searched for available data in the present review. A database search yielded more than 100 articles out of which 45 were included based on the core data. The role of NTs and NTRs in dental diseases is less explored and this was the very first attempt to collect the literature data of NTs and NTRs pertaining to head and neck tumors. The results and subsequent conclusions were extracted and reviewed. Expression of NTs and NTRs in neuronal and non-neuronal tissue is a spatial and time-bound event like odontogenesis. Recently NTs and NTRs expressions were detected in a few head and neck tumors. Unraveling the molecular signaling pathway of NTs and NTRs in head and neck tumors will help in elucidating the molecular pathogenesis and the prognosis, therefore, paving a path to expand our knowledge to understand and develop therapies for many pathologic conditions.